The economic recession and mental health: analysis of the Portuguese situation - Viseu,João Nuno Ribeiro (2015)
Recently, some European countries (e.g., Greece, Ireland, and Portugal) suffered an economic recession, mainly due to problems in the banking system and high sovereign debt. Economic stressors, such as economic hardship, financial threat, and financial well-being may contribute negatively to individuals' psychological health, potentiating the appearance of negative psychological outcomes. The objective of the current research was to analyze the impact of economic stressors (i.e., economic hardship, financial threat, and financial well-being) on mental health indicators (i.e., stress, anxiety, and depression). Data from a sample of 729 Portuguese participants was collected, 482 (66.1%) women and 247 (33.9%) men, with an average age of, approximately, 37 years old (M=36.99; SD=12.81). Structural Equation Modeling (SEM) was used to examine the relationship between the economic stress and psychological health variables. The obtained results demonstrated a model with economic hardship and financial threat as significant predictors of stress, anxiety, and depression, while financial well-being was a significant predictor of anxiety and depression. Some implications of these results are discussed.